Laser-assisted Operculectomy in an 8-Year-old Child Using Diode Laser: A Case Report - Sourav Bhattacharjee1 , Susant Mohanty2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The past years in dentistry has seen the growth of the use of laser advance by leaps and bounds. Thoughsoft-tissue laser was originally presented, but with the development of new-generations of laser technology,lasers are equally effective on hard tissues. Lasers have a plethora of uses in pediatric dentistry includingprevention of caries, prompt diagnosis, restoration of cavities, managing cases of trauma to teeth alongwith various minor oral surgical procedures. Lasers are advantageous for being more rapid, more precise,sterile and providing a bloodless field of surgery and are also better accepted by pediatric patients and theirparents. In the same light, treatment of a pediatric patient becomes easier it is less fear-inducing for thechild thus increasing co-operative behavior. The soft tissue covering over a partially erupted tooth is knownas pericoronal flap or gingival operculum. Surgical removal of the latter is termed as Operculectomy. Thefollowing text reports a case of Operculectomy performed using a diode laser in the pediatric operatory.